Cannabis Use Behaviors and Related Harms among Adults in Thailand by Sex Assigned at Birth and Age Groups - Jayuphan, Jirawan; Assanangkornchai, Sawitri; Wichaidit, Wit (Journal of Health Science and Medical Research, 2024)
Objective: The objectives of this study were to describe: 1) cannabis use behaviors; 2) self-reported cannabis-related harms and harmful behaviors among adults in Thailand, stratified by sex (assigned at birth) and age groups. Material and Methods: A nationally-representative survey among adults in Thailand in May 2023 was conducted. Data using descriptive statistics with sampling weight adjustment was analyzed. Results: Among the study participants (n=2,191 participants), approximately 15% of the participants were current cannabis users (estimated number: 7.5 million people aged 20 or over nationwide). Former and current users reported recreation or other non-medical purposes as the primary purposes of use (93% combined). Ingestion was the most common method of cannabis use. Male participants were more likely than female participants in all age groups to report using smoked cannabis. The most common harmful was riding a motorcycle after having used cannabis, although virtually no participants reported road accidents after same-day cannabis use. Conclusion: This study’s data provided basic information for relevant stakeholders. However, the lack of detailed information, the potential influence of social desirability, and the limited temporal generalizability should be considered in the interpretation of this study’s findings.